Developing Wetland Contextual Interactive Learning Media on Numbers Using Drill and Practice Method - Harja Santana Purba; Ati Sukmawati; Nuruddin Wiranda; Yuni Suryaningsih; Rizaldi Aprilian (Jurnal Pendidikan Matematika, 2022)
Textbooks used in schools today are available in both print and digital versions. The use of the digital version is not much different from the printed version, which is accessed page by page. The more technology develops, the more learning facilities and infrastructure are developed. Currently the availability of interactive technology that allows students and books to interact with each other. Interactive books can be designed to respond to student activities as a teacher responds to students. The purpose of this study was to develop interactive media on number material for class VII students with a drill and practice approach. The content of teaching materials has wetland content, including information on fruits, fish and handicrafts. This interactive media was developed using HTML, CSS, Javascript, Scratch, Mathjax, JSON, and Firebase technologies. The learning approach uses the drill and practice method. This interactive media was tested to organize online learning during the Covid-19 pandemic. Based on the results of the study, it was found that student learning outcomes showed the overall average score was above the KKM of the subjects, namely the average value of learning outcomes was 75.80 from the KKM of 75.00. The results of teacher and student responses showed a positive response to the developed interactive media.